The Influence of Implementation of Corporate Social Responsibility (CSR) on Increasing MSME Income (Case Study at PT PLN (Persero) UP3 Jambi) - Nafisah Ainun Nisa; Nela Safelia; Susfa Yetti (Indonesian Journal of Economic & Management Sciences, 2023)
This study aims to determine influence of the implementation of corporate social responsibility (CSR) of the Training and Coaching Program, Capital Loans, and Assistance on Increasing MSME Income (a case study at PT PLN UP3 (Persero) Jambi).  The sampling technique used is simple random sampling with sampling using the slovin formula.  Respondents in this study amounted to 51 fostered MSME partners.  The type of data used is in the form of primary data.  The data analysis used in this study is multiple linear regression analysis and by using the SPSS version 25 application to perform data processing.  The results of the study show that training and coaching have an effect on increasing MSME income.  Meanwhile, capital loans and assistance have no effect on increasing MSME income